The Usability of the Plan Quality Index to Support Evaluation of Community Health Action Plans. Issue 11 (30th December 2020) - Courie, Anna F; Tate, Judith
ABSTRACT: Introduction: The U.S. Army requires community health coalitions to develop targeted action plans in order to more effectively address top public health priorities. Reviews of community action plans indicate that they are often poorly developed and not fully implemented. To date, the U.S. Army has not implemented a standardized tool or process to evaluate action plans and provide recommendations for improvement to local installations. The Plan Quality Index (PQI) is an evidence-based, standardized tool that has been used successfully by technical experts to review and improve community action plans related to the prevention of obesity, injury and violence, and cancer. Materials and Methods: The objective of this project was to determine the usability of the PQI and to provide recommendations for improving community health action plans focused on injury prevention for the U.S. Army. Five Health Promotion Project Officers and one Health Promotion Project Assistant at Army Public Health Center were trained on the PQI and reviewed injury prevention action plans for 17 installations. After using the PQI to assess injury prevention action plans, the individuals were given a System Usability Scale (SUS) survey to assess the usability of the PQI. Results: Results of the SUS survey can range from 0 to 100, but do not represent percentages. A score of 65 indicates "greater than average" usability. Participant scores on the SUS demonstrated that the PQI has a high degree of usability. Mean usability was calculated at 83.3 (range 72.5–97.5, median 85, sd +/− 9.3). Conclusion: The PQI demonstrated a high level of usability by technical experts for providing feedback and recommendations regarding community health action plans for injury prevention in the U.S. Army. As a result, the PQI may be beneficial as a standard tool for community health improvement planning and consultation throughout the Army Public Health Center.